Retracted: Quercetin Decreases Liver Damage in Mice with Non‐Alcoholic Steatohepatitis. (21st March 2013) - Marcolin, Éder; Forgiarini, Luiz Felipe; Rodrigues, Graziella; Tieppo, Juliana; Borghetti, Greice Stefani; Bassani, Valquiria Linck; Picada, Jaqueline Nascimento; Marroni, Norma Possa
Abstract: Non‐alcoholic steatohepatitis (NASH) is a frequent condition in obese patients that may progress to end‐stage liver disease. This study was designed to evaluate the modulation of this condition by use of quercetin (Q), a flavonoid largely found in vegetable foods, with known anti‐inflammatory and antioxidant properties, in the experimental model of non‐alcoholic steatohepatitis (NASH) using a diet deficient in methionine and choline (MCD). Male C57BL6 mice were divided into four groups (n = 16): (i) Control plus vehicle (control ration plus carboxymethylcellulose 1% used as vehicle, CO + V); (ii) Control ration plus Q 50 mg/kg (CO + Q); (iii) MCD diet plus vehicle (NASH + V); and (iv) MCD diet plus Q (NASH + Q). Diets were administered for 4 weeks. At the end of the experimental period, liver alterations, bioindicators of oxidative stress and DNA damage were assessed. NASH was diagnosed in 100% of the mice that were fed the MCD diet. In addition, a significant increase in DNA damage in liver tissue from NASH + V group was observed in comparison with CO + V. The group NASH + Q showed a significant decrease in hepatic damage enzymes, lipoperoxidation, DNA damage and a lower degree of macrovesicular steatosis, ballooning and inflammatory process. These findings suggest that Q may have protective effects by improving liver integrity in NASH.